The operative cooperation and nursing in transradial intervention for cerebrovascular diseases (经桡动脉入路行脑血管介入治疗的手术配合与护理) - SHI Lijuan (施李娟); HU Yaqin (胡亚琴); MIAO Dan (苗丹); SONG Zongye (宋宗叶); WANG Xiaoyan (王晓燕); JIANG Wei (江薇) (中西医结合护理)
Objective To summarized the operative cooperation and nursing management in transradial intervention for cerebrovascular diseases. Methods To retrospectively analyze the clinical data of 255 patients who underwent transradial intervention for cerebrovascular diseases. Key points in preoperative preparation included evaluation of patient condition, drugs inspection and catheter devices and instrument preparation. Nurses should take good cooperation in performing catheter placement, surgical position placement, heparinization, microcatheter shaping and other nursing procedure. Efforts should also be made in prevention of intraoperative complications and postoperative nursing of puncture site complications. Results Surgical operation was successful in 214 patients. There were 16 cases of slight swelling and 5 cases of severe swelling, and there was no case of adverse complications. Conclusion The accurate and effective operative cooperation and nursing is able to guarantee a successful transradial intervention for cerebrovascular diseases. (目的 总结经桡动脉入路(TRA)行脑血管介入治疗手术的配合和护理经验。方法 回顾性分析225例经桡动脉入路行脑血管介入治疗患者临床资料, 总结手术配合和护理经验。护理人员术前完善患者评估、导管室常用药品和器械准备工作; 术中积极配合完成导管留置、体位摆放、肝素化、微导管塑型等操作, 同时加强术中并发症预防; 术后完善穿刺点护理。结果 225例手术成功214例, 末梢轻度肿胀16例, 重度肿胀5例, 无恶性并发症。结论 精准有效的术中配合是经桡动脉入路行脑血管介入治疗成功的有效保障。)